Resin composition for bonded magnets and bonded magnet using the same

CN122996489APending Publication Date: 2026-10-27TODA KOGYO CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202580023183.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2025-03-05
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,PPS树脂为低韧性

Benefits of technology

[0020]使用本实施方式涉及的粘结磁体用树脂组合物成型而得的成型品中, Br(剩余磁通密度)这样的磁特性不降低。另外,该成型品即使在暴露于热环境后耐冲击性也优异,而且具有高的耐冷热冲击性。因此,该成型品即使在严酷的环境下也能够使用。因此,本实施方式涉及的粘结磁体用树脂组合物适合作为粘结磁体用材料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

According to the present embodiment, a resin composition for bonded magnets having excellent impact resistance and cold-heat shock resistance without reducing magnetic properties can be provided. A resin composition for bonded magnets containing at least a magnetic powder, a PPS resin, and a polyamide-based thermoplastic elastomer is provided. The polyamide-based thermoplastic elastomer has a melting point of 130°C to 170°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to resin compositions for bonding magnets and bonding magnets using the resin compositions. Background Technology

[0002] Bonded magnets offer numerous advantages. For instance, they are lighter and have better dimensional accuracy compared to sintered magnets. Furthermore, bonded magnets are easier to mass-produce for complex shapes compared to sintered magnets. Therefore, bonded magnets are widely used in various applications such as toys, office equipment, audio equipment, and motors.

[0003] In the manufacturing process of bonded magnets, typically, rubber or plastic materials are first mixed with magnetic powder. The resulting mixture is then molded in a magnetic field. Alternatively, the mixture may sometimes be molded mechanically.

[0004] In recent years, the productivity and reliability of various materials and equipment have significantly improved. This increased functionality in these materials and equipment necessitates higher performance in the bonded magnets used. Such performance improvements include increased productivity, enhanced mechanical strength, and improved magnetic properties.

[0005] For example, in vehicles, bonded magnets are used as rotors and sensors. Relatedly, for long device lifespan and use at high speeds, the rotors and sensors require high heat resistance and high mechanical strength. Therefore, bonded magnets utilizing PPS resin are used as the binder resin. PPS resin is known to have high heat resistance. Furthermore, it is known that even at high temperatures, the mechanical properties of PPS resin decrease little. However, PPS resin has low toughness. Therefore, there are concerns about the development of cracks, such as those immediately after injection molding, or cracks in hot and cold environments (thermal shock), in bonded magnets using PPS resin. Therefore, high impact resistance and high resistance to thermal shock are strongly required for this bonded magnet.

[0006] For example, Japanese Patent Application Publication No. 2013-253219 discloses a method for manufacturing a composite for bonded magnets with high magnetic strength. In this method, PA resin or PPS resin is mixed with a block copolymer containing styrene and butene units as constituent components in a predetermined ratio. This allows the manufacture of a composite for bonded magnets with high magnetic strength exhibiting excellent flowability and excellent mechanical strength.

[0007] Japanese Patent Application Publication No. 4-44304 discloses a method for manufacturing a composite for bonding magnets with excellent resistance to thermal shock. In this method, modified polyolefins and glass fibers are added to PPS resin.

[0008] Japanese Patent Application Publication No. 9-219312 discloses a method for manufacturing a composite for bonding magnets with high magnetic strength. In this method, PPS resin and vinylidene fluoride-based rubber are mixed in a specified ratio.

[0009] Therefore, it is possible to manufacture composite materials for bonded magnets with high magnetic strength and excellent flowability and excellent mechanical strength. Summary of the Invention

[0010] According to the researchers, the bonded magnet using PPS resin disclosed in Japanese Patent Application Publication No. 2013-253219 has issues regarding heat resistance and mechanical strength. Furthermore, Japanese Patent Application Publication No. Hei 4-44304 aims to improve resistance to thermal shock. However, this technology cannot avoid a decrease in magnetic properties. According to the technology disclosed in Japanese Patent Application Publication No. Hei 9-219312, the mechanical strength of the molded article is improved. However, there are concerns about the generation of corrosive gases from vinylidene fluoride-based rubber. Therefore, this molded article is not suitable for use in high-temperature environments.

[0011] Therefore, a technical challenge in this embodiment is to obtain a resin composition for bonding magnets that exhibits excellent heat resistance, impact resistance, and thermal shock resistance without reducing magnetic properties.

[0012] The aforementioned technical issues can be addressed through the following implementation method.

[0013] That is, the resin composition for bonding magnets according to this embodiment includes at least magnetic powder, PPS resin, and polyamide-based thermoplastic elastomer. The melting point of the polyamide-based thermoplastic elastomer is 130°C to 170°C (first embodiment).

[0014] Furthermore, in the resin composition for bonding magnets in the first embodiment, the Shore hardness D of the polyamide thermoplastic elastomer can be 35 to 60 (second embodiment).

[0015] Furthermore, in the resin composition for bonding magnets in the first or second embodiment, the tensile elongation of the polyamide thermoplastic elastomer can be 400% or more (third embodiment).

[0016] Furthermore, in any of the first to third embodiments of the resin composition for bonding magnets, the content of the polyamide thermoplastic elastomer relative to the PPS resin may be 3.0 to 20.0% by weight (fourth embodiment).

[0017] Furthermore, in any of the first to fourth embodiments of the resin composition for bonding magnets, the content of the above-mentioned PPS resin may be 5 to 30% by weight (fifth embodiment).

[0018] Furthermore, in any of the first to fifth embodiments of the resin composition for bonding magnets, the content of the polyamide-based thermoplastic elastomer may be 0.40 to 2.60% by weight (sixth embodiment).

[0019] Furthermore, the bonded magnet involved in this embodiment is a bonded magnet obtained by molding using the bonded magnet resin composition of any one of the first to sixth embodiments (seventh embodiment).

[0020] In the molded article obtained using the resin composition for bonding magnets according to this embodiment, magnetic properties such as Br (remanent magnetic flux density) are not reduced. Furthermore, the molded article exhibits excellent impact resistance even after exposure to a hot environment, and also possesses high resistance to thermal shock. Therefore, the molded article can be used even in harsh environments. Therefore, the resin composition for bonding magnets according to this embodiment is suitable as a material for bonding magnets. Detailed Implementation

[0021] The following describes this embodiment in detail.

[0022] The resin composition for bonding magnets according to this embodiment contains at least magnetic powder, PPS resin and polyamide thermoplastic elastomer.

[0023] The magnetic powder used in this embodiment is not particularly limited. Magnetic powders commonly used for bonding magnets can be used. Examples of magnetic powders used include ferrite particle powder, rare-earth magnetic powder, and soft magnetic ferrite particle powder.

[0024] The ferrite particle powder is preferably a magnetoplumb-type ferrite particle powder. Magnetoplumb-type ferrite particle powder is represented by the formula AO·nFe₂O₃ (where A is Ba, Sr, or Ba-Sr, and n = 5.0–6.5). Examples of ferrite particle powders represented by this formula include barium ferrite particle powder, strontium ferrite particle powder, and barium-strontium ferrite particle powder. These ferrite particle powders may contain one or more elements selected from Ti, Mn, Al, La, Zn, Bi, and Co as constitutive elements. The content of this constitutive element in the ferrite particle powder is, for example, in the range of 0.1–7.0 mol%.

[0025] The average particle size of the ferrite powder is preferably 1.0–5.0 μm, more preferably 1.0–2.0 μm. The BET specific surface area of ​​the ferrite powder is preferably 1–10 m². 2 / g, more preferably 1-5m 2 / g. The coercivity iHc of the ferrite particle powder is preferably 119–557 kA / m (1500–7000 Oe), more preferably 119–398 kA / m (1500–5000 Oe). The remanent magnetization of the ferrite particle powder is preferably 100–300 mT (1000–3000 G), more preferably 100–200 mT (1000–2000 G).

[0026] Rare earth magnetic powders are intermetallic compounds. Intermetallic compounds contain at least one rare earth element and at least one transition metal as constituent elements. Examples of such rare earth magnetic powders include cobalt-based, iron-boron-based, and iron-nitrogen-based magnetic powders. In particular, when using iron-boron-based and iron-nitrogen-based magnetic powders, bonded magnets with excellent magnetic properties can be obtained.

[0027] The average particle size of the rare earth magnetic powder is preferably 1–120 μm, more preferably 1–80 μm. The BET specific surface area of ​​the rare earth magnetic powder is preferably 0.5–5 m². 2 / g, more preferably 0.5-3m 2 / g. The coercivity iHc of the rare earth magnetic powder is preferably 239–1591 kA / m (3.0–20 kOe), more preferably 318–1114 kA / m (4.0–15 kOe). The remanent magnetization of the rare earth magnetic powder is preferably 0.3–1.8 mT (3.0–18 kG), more preferably 0.5–1.3 mT (5.0–13 kG).

[0028] Examples of soft magnetic ferrite particle powders include Mn-Zn ferrite, Ni-Zn ferrite, Ni-Zn-Cu ferrite, Mn-Mg ferrite, carbonyl iron powder, and iron-silicon-aluminum powder. Additionally, soft magnetic ferrites with compositions that vary according to the frequency of the electromagnetic wave used can also be used.

[0029] The average particle size of the soft magnetic ferrite powder is preferably 1 to 150 μm, more preferably 1 to 50 μm.

[0030] In order to suppress the deterioration of magnetic properties caused by oxidation, improve compatibility with resin, and improve the strength of molded articles, it is preferable to perform various surface treatments on these magnetic powders.

[0031] Examples of materials that can be used for surface treatment include silane-based coupling agents, titanium-based coupling agents, aluminum-based coupling agents, siloxane polymers, organophosphate-based surface treatment agents, and inorganic phosphate-based surface treatment agents. In particular, by pretreating the surface of magnetic powder using silane-based coupling agents, the strength of the molded product can be further improved.

[0032] The polyamide-based thermoplastic elastomer used in this embodiment contains polyamide as a hard segment. Examples of soft segments included in the polyamide-based thermoplastic elastomer include polyether, polyester, polyether ester, polybutanediol, and polypropylene glycol. One of these exemplified polyamide-based thermoplastic elastomers can be used alone. Alternatively, two or more of these polyamide-based thermoplastic elastomers can be used in combination.

[0033] When polyamide-based thermoplastic elastomers are mixed with PPS resin, the elastomers are easily and uniformly dispersed in the PPS resin. Therefore, by using polyamide-based thermoplastic elastomers, molded articles with excellent moldability and excellent physical properties can be obtained.

[0034] The melting point of the polyamide-based thermoplastic elastomer used in this embodiment is, for example, 130°C to 170°C. By keeping the melting point of the polyamide-based thermoplastic elastomer within the above range, molded articles with excellent impact resistance, thermal shock resistance, and heat resistance can be obtained. The melting point of the polyamide-based thermoplastic elastomer is preferably 150°C to 165°C.

[0035] In this embodiment, the Shore hardness D of the polyamide-based thermoplastic elastomer is preferably 35 to 60. Shore hardness D is an indicator of the hardness of plastics or rubber. This indicator is measured using a type D hardness tester. A higher Shore hardness D value indicates higher hardness. By making the Shore hardness D of the polyamide-based thermoplastic elastomer within the above range, molded articles with excellent impact resistance and resistance to thermal shock can be obtained. More preferably, the Shore hardness D of the polyamide-based thermoplastic elastomer is 40 to 58, and even more preferably 45 to 55.

[0036] The elongation at break of the polyamide-based thermoplastic elastomer is preferably 400% or more. By achieving an elongation at break of 400% or more, molded articles with excellent resistance to thermal shock can be obtained. More preferably, the elongation at break of the polyamide-based thermoplastic elastomer is 500% or more.

[0037] The PPS resin used in this embodiment is not particularly limited. Preferably, the average molecular weight of the PPS resin is in the range of 10,000 to 100,000. Low molecular weight PPS resin has low melt viscosity. Therefore, when using low molecular weight PPS resin, the moldability of the resin composition for bonding magnets as an injection molding composition is excellent. On the other hand, the physical properties such as strength of the resin composition for bonding magnets are poor. In contrast, high molecular weight PPS resin has high viscosity. Therefore, when using high molecular weight PPS resin, the physical properties of the resin composition for bonding magnets are excellent, unlike those of low molecular weight PPS resin. On the other hand, when the filling amount of magnetic powder is high, its moldability is poor. Furthermore, the molecular structure of the PPS resin is not particularly limited. PPS resin having either a cross-linked or linear molecular structure can be used.

[0038] As the PPS resin, a resin with an appropriate melt viscosity corresponding to the magnetic powder can be selected. Relatedly, the preferred melt viscosity range for the PPS resin is 5–200 Pa·s at 310°C. By keeping the melt viscosity within the above range, a resin composition for bonding magnets with good flowability and suitable for injection molding can be obtained. Furthermore, the resulting resin composition for bonding magnets can also possess sufficient mechanical strength.

[0039] In the resin composition for bonding magnets according to this embodiment, the content of polyamide-based thermoplastic elastomer relative to PPS resin is preferably 3.0 to 20.0% by weight. By keeping the content of polyamide-based thermoplastic elastomer relative to PPS resin within the above range, a molded article with good impact resistance and good resistance to thermal shock can be obtained. In addition, the flexural strength of this molded article is also excellent. When the content of polyamide-based thermoplastic elastomer relative to PPS resin exceeds 20.0%, the heat resistance of the molded article sometimes decreases. The content of polyamide-based thermoplastic elastomer relative to PPS resin is more preferably 4.0 to 19.0% by weight, and even more preferably 5.0 to 18.0% by weight.

[0040] The resin composition for bonding magnets according to this embodiment preferably contains 0.40 to 2.60% by weight of a polyamide-based thermoplastic elastomer. By keeping the content of the polyamide-based thermoplastic elastomer within the above range, a molded article with good impact resistance and resistance to thermal shock can be obtained. In addition, the flexural strength of this molded article is also excellent. When the content of the polyamide-based thermoplastic elastomer exceeds 2.60%, the heat resistance of the molded article sometimes decreases. The content of the polyamide-based thermoplastic elastomer is more preferably 0.60 to 2.45% by weight, and even more preferably 0.70 to 2.40% by weight.

[0041] The resin composition for bonding magnets according to this embodiment preferably contains 5 to 30% by weight of PPS resin. By keeping the content of PPS resin within the above range, the resin composition for bonding magnets has sufficient fluidity. Therefore, good molded articles can be easily obtained. When the content of PPS resin exceeds 30% by weight, the magnetic properties become lower. The content of PPS resin is more preferably 7 to 25% by weight, and even more preferably 10 to 20% by weight.

[0042] The content of magnetic powder in the resin composition for bonding magnets is preferably 69.6 to 94.5% by weight. By keeping the content of magnetic powder within the above range, bonded magnets with excellent magnetic properties can be obtained. When the content of magnetic powder exceeds 94.5% by weight, the formability of the resin composition, such as flowability, may decrease. Or, the mechanical strength of the resulting bonded magnet may decrease. The content of magnetic powder is more preferably 74.6 to 92.5% by weight, and even more preferably 79.6 to 89.5% by weight.

[0043] When using the aforementioned ferrite particle powder as the magnetic powder, the remanent magnetic flux density Br of the resin composition for bonding magnets according to this embodiment is preferably 230 mT (2300 G) or more, and more preferably 245 mT (2450 G) or more. This remanent magnetic flux density Br is determined by the magnetic measurement method described later. The coercivity iHc of the resin composition for bonding magnets is preferably 119–279 kA / m (1500–3500 Oe), and more preferably 127–259 kA / m (1600–3250 Oe). The maximum energy product (BH)max of the resin composition for bonding magnets is preferably 10.3 kJ / m. 3 (1.30 MGOe) or higher, more preferably 10.7 kJ / m 3 (1.35MGOe) or above.

[0044] When using the aforementioned rare-earth magnetic powder as the magnetic powder, the remanent magnetic flux density Br of the resin composition for bonding magnets according to this embodiment is preferably 300 mT (3000 G) or more, more preferably 350 mT (3500 G) or more. The value of this remanent magnetic flux density Br is determined by the magnetic measurement method described later. The coercivity iHc of the resin composition for bonding magnets is preferably 636–955 kA / m (8000–12000 Oe), more preferably 676–915 kA / m (8500–11500 Oe). The maximum energy product (BH)max of the resin composition for bonding magnets is preferably 15.9 kJ / m. 3 (2.00 MGOe) or higher, more preferably 19.9 kJ / m 3 (2.50MGOe) or above.

[0045] Next, the method for manufacturing the resin composition for bonding magnets according to this embodiment will be described.

[0046] The resin composition for bonding magnets according to this embodiment can be obtained by a known method for manufacturing resin compositions for bonding magnets. For example, firstly, magnetic powder, PPS resin components, and a polyamide-based thermoplastic elastomer are uniformly mixed. Then, the resulting mixture is melt-kneaded using, for example, a kneading extruder. The resulting mixture is then pulverized or cut into granules or pellets.

[0047] The resin composition for bonding magnets described in this embodiment may contain, for example, lubricants for plastic molding or various stabilizers in order to improve moldability, improve heat resistance, prevent oxidative deterioration, or obtain rust prevention.

[0048] Examples of lubricants used include substances containing carboxyl-saturated or unsaturated fatty acid systems such as propionic acid, stearic acid, linoleic acid, oleic acid, malonic acid, glutaric acid, adipic acid, maleic acid, and fumaric acid, as well as compounds derived from these substances. Examples of compounds derived from these substances include metal soaps containing calcium stearate, magnesium stearate, and lithium stearate; fatty acid amides containing hydroxydistearate, ethylene bislaurate, and ethylene bisoleate; waxes such as paraffin wax; polysiloxanes containing dimethylpolysiloxane and silicone oil; and fluorinated compounds such as fluorinated oils.

[0049] To suppress heat-induced degradation, it is preferable to add antioxidants as stabilizers. Examples of usable antioxidants include metal passivators and stabilizers. Examples of metal passivators include N,N'-bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionylhydrazine]. Examples of stabilizers include hindered amine stabilizers, hindered / unhindered phenolic stabilizers such as pentaerythritol tetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], phosphite stabilizers, and thioether stabilizers. It is particularly effective to combine hindered / unhindered phenolic stabilizers with phosphite stabilizers or metal passivators.

[0050] The antioxidant is preferably contained in the range of 0.1 to 1.0 wt%, more preferably in the range of 0.2 to 0.8 wt%, relative to the total amount of the resin composition.

[0051] In addition, known release agents, such as those containing zinc stearate and calcium stearate, can be added to the resin as needed.

[0052] To reduce the generation of corrosive gases, the resin composition for bonding magnets according to this embodiment may contain hydrotalcite powder.

[0053] Hydrotalcite powder has the general formula: [M 2+1-x M 3+ x (OH)2[A n- x / n ·mH2O] (where M 2+ This indicates that it contains, for example, Mg. 2+ Co 2 + Ni 2+ and Zn 2+ A divalent metal ion. M 3+ Indicates containing, for example, Al 3+ Fe 3+ and Cr 3+ A trivalent metal ion. n- This indicates the presence of, for example, OH. - Cl - CO3 2- and SO4 2- Interlayer anions. x satisfies 0 < x < 1. n is the valence of A. m satisfies 0 ≤ m < 1. ) represents a layered compound. Preferably, the divalent metal ion is Mg. 2+ Furthermore, trivalent metal ions containing Al are preferred. 3+ Mg-Al type hydrotalcite. Some or all of these metal ions can be replaced by other metal ions.

[0054] The hydrotalcite powder contains plate-shaped particles. The average plate diameter is 0.01–1.0 μm, preferably 0.02–0.8 μm, and more preferably 0.03–0.7 μm. When the average plate diameter is less than 0.01 μm, the dispersibility in the resin is insufficient. When it exceeds 1.0 μm, it is difficult to produce plate-shaped particles industrially.

[0055] The preferred BET specific surface area of ​​hydrotalcite powder is 1–150 m². 2 / g, more preferably 5-100mg 2 / g, more preferably 8-50m 2 / g. Has a concentration of less than 1m 2 Hydrotalcite particles with a BET specific surface area of ​​ / g are difficult to obtain industrially. BET specific surface areas exceeding 150m² are also rare. 2 At a concentration of / g, particle aggregation becomes intense. As a result, particles are difficult to disperse uniformly in the resin.

[0056] Hydrotalcite powder can be coated with at least one surface treatment agent selected from higher fatty acids, anionic surfactants, higher fatty acid phosphates, coupling agents, and polyol esters, as needed. Coating with a surface coating improves the dispersibility of the hydrotalcite powder in the resin.

[0057] The content of hydrotalcite powder in the resin composition for bonding magnets according to this embodiment is preferably 0.1 to 25.0% by weight relative to PPS resin. When the content of hydrotalcite powder relative to PPS resin is within the above range, the effect of reducing corrosive gases can be obtained. When the content of hydrotalcite powder relative to PPS resin exceeds 25.0% by weight, the non-magnetic components increase. As a result, mechanical properties, magnetic properties, or flowability may decrease. The content of hydrotalcite powder relative to PPS resin is more preferably 0.5 to 15.0% by weight, and even more preferably 1.0 to 5.0% by weight.

[0058] The resin composition for bonding magnets according to this embodiment preferably contains 0.01 to 4.0% by weight of hydrotalcite powder. When the content of hydrotalcite powder is within the above range, the effect of reducing corrosive gases can be obtained. When the content of hydrotalcite powder exceeds 4.0% by weight, the non-magnetic components increase. As a result, mechanical properties, magnetic properties, or flowability may decrease. The content of hydrotalcite powder is preferably 0.10 to 2.5% by weight, more preferably 0.20 to 1.0% by weight.

[0059] There are no particular limitations on the molding method used to obtain molded articles of the resin composition for bonding magnets using this embodiment. For example, known methods can be used individually depending on the material properties of the resin composition for bonding magnets, the molding purpose, or the intended use. Alternatively, multiple known methods can be used in combination. Examples of known methods include transfer molding, injection molding, extrusion molding, blow molding, calendering, T-die molding, blow molding, vacuum molding, lamination, spraying, foaming, die-fitting, and SMC molding. In particular, injection molding or extrusion molding is preferred in resin compositions for bonding magnets using thermoplastic resins. These methods are applied to many industrial parts. According to these methods, continuous and high-speed mass production can be implemented.

[0060] Example

[0061] The following are representative embodiments of this implementation. However, the implementation of this application is not limited to these embodiments.

[0062] The average particle size of the ferrite powder used in this embodiment was measured using a Sub-Sieve Sizer Model 95 (made by Fisher Scientific).

[0063] The BET specific surface area of ​​the ferrite particle powder used in this embodiment was measured using a "Macsorb model-1201 fully automatic specific surface area meter" (manufactured by Mountech Co., Ltd.).

[0064] The melting point of the polyamide-based thermoplastic elastomer used in this embodiment was determined according to ISO 11357.

[0065] The Shore hardness D of the polyamide-based thermoplastic elastomer used in this embodiment was determined according to ISO 868.

[0066] The tensile elongation of the polyamide-based thermoplastic elastomer used in this embodiment was determined according to ISO 527.

[0067] The physical properties of the polyamide-based thermoplastic elastomers used in this embodiment are shown in Table 1.

[0068]

[0069] Regarding the melt flow rate (MFR) of the resin composition for bonding magnets, melting was carried out at 330°C according to JIS K710. Then, the MFR was determined by measurement under a 10 kg load.

[0070] The molding density of the bonded magnet was determined as follows. First, using a J55AD injection molding machine manufactured by Nippon Steel Co., Ltd., a core was formed in a mold with a diameter of 25 mm and a height of 10.5 mm, using a resin composition for bonding magnets. Then, the core was measured using an electronic hydrometer EW-120 SG (manufactured by Yasuda Seiki Co., Ltd.). The molding density of the bonded magnet was thus determined.

[0071] The magnetic properties of the bonded magnet (remanent magnetic flux density Br, coercivity iHc, coercivity bHc, and maximum energy product (BH)max) were determined as follows. First, using a resin composition for bonding magnets as the material, a J55AD injection molding machine manufactured by Nippon Steel Co., Ltd. was used. The molding process was carried out in a mold with a diameter of 25 mm and a height of 10.5 mm, while the magnet was oriented in a magnetic field of 318.3 kA / m (4 kOe). Then, the molded body was measured using a "DC magnetization characteristic automatic recording device 3257" (manufactured by Yokokawa Hokushin Electric Co., Ltd.) in a magnetic field of 1114.1 kA / m (14 kOe). The aforementioned magnetic properties were then determined.

[0072] The physical properties of the bonded magnets were determined using a test piece A with a total length of 80 mm, a total width of 12.7 mm, and a thickness of 3.2 mm, and a cylindrical test piece B with an outer diameter of Φ30 mm, an inner diameter of 26 mm, and a height of 30 mm. These test pieces A and B were obtained by injection molding the bonded magnets with a resin composition using a J55AD type injection molding machine manufactured by Nippon Steel Corporation.

[0073] The flexural strength and IZOD impact strength of the molded body A, which was formed using a resin composition for bonding magnets, were determined according to ASTM D790 and D256 standards using a computer-controlled precision universal testing machine AG-1 manufactured by Shimadzu Corporation and a NO.158 manufactured by Yasuda Seiki Co., Ltd.

[0074] In the heat aging test of molded body A, which was formed using a resin composition for bonding magnets, molded body A was exposed to a thermal environment of 150°C for 1000 hours using an oven. Then, molded body A was placed at room temperature for 24 hours. The flexural strength and IZOD impact strength were then measured in the same manner as described above. Furthermore, the strength retention rate (%) was confirmed by comparing the strength before and after thermal exposure.

[0075] In the thermal shock resistance test of molded body B, which was formed using a resin composition for bonding magnets, a thermal shock apparatus TSA-73EL (manufactured by ESPEC Corporation) was used. The operation was performed for 1000 cycles, with a temperature range of -20°C to 120°C (holding time at each temperature being 30 minutes) as one cycle. The crack initiation rate of molded body B was then confirmed by visual observation.

[0076] Example 1

[0077] Ferrite particle powder (average particle size 1.20 μm, BET value: 1.75 μm) 2 / g, coercivity 226kA / m (2850Oe), saturation magnetization 822Am 2 An aminoalkyl silane coupling agent was added to the mixture at a concentration of 72 emu / g. The resulting mixture was heated and mixed at 120°C until homogeneous. This yielded a surface-treated ferrite particle powder. PPS resin (average molecular weight: 30,000, melt viscosity: 30 Pa·s at 310°C) and polyamide thermoplastic elastomer 1 (melting point: 135°C, Shore hardness D: 40, elongation at break: 400% or more) were added to this surface-treated ferrite particle powder. The resulting mixture was thoroughly mixed using a Henschel mixer. The proportions are shown in Table 2. This yielded a mixture of resin compositions for bonding magnets.

[0078] The resulting mixture of resin composition for bonding magnets is quantitatively fed into a biaxial mixer. The mixture in the mixer is kneaded at the melting temperature of PPS resin. The resulting compound is removed in wire form. The removed wire is cut into granules of 2mm diameter × 3mm. This yields the resin composition for bonding magnets.

[0079] The resin content ratios of the obtained resin compositions for bonding magnets are shown in Table 3. Additionally, the MFR of the resin compositions for bonding magnets, the molding density of the bonded magnets, and the magnetic properties are shown in Table 4.

[0080] Table 5 shows the results of the flexural strength, IZOD impact strength, and strength retention rate of molded specimen A before and after the heat aging test, obtained by injection molding of the resin composition for bonding magnets. Table 5 also shows the yield rate of molded specimen B in the thermal shock resistance test.

[0081] Examples 2-10

[0082] The formulation of ferrite magnetic powder, PPS resin and polyamide thermoplastic elastomer was modified in various ways as described in Table 2. Otherwise, the resin composition for bonding magnets was prepared in the same manner as in Example 1 above.

[0083]

[0084]

[0085]

[0086]

[0087] Comparative Example 1

[0088] The resin composition for bonding magnets was prepared in the same manner as in Example 1 above, except that the composition was changed without using polyamide-based thermoplastic elastomers.

[0089] Comparative Example 2

[0090] The resin composition for bonding magnets was prepared in the same manner as in Example 1 above, except that the polyamide thermoplastic elastomer was changed to polyamide thermoplastic elastomer 4 and the composition was modified in various ways as described in Table 6.

[0091] Comparative Examples 3-7

[0092] The resin composition for bonding magnets was prepared in the same manner as in Example 1 above, except that the thermoplastic elastomer was changed to thermoplastic elastomers 5 to 9, and the composition was modified in various ways as described in Table 6.

[0093] The resin content ratios of the obtained resin compositions for bonding magnets are shown in Table 7. Furthermore, the properties of these compositions are shown in Table 8. In addition, the test results of the molded test pieces obtained by injection molding of the resin compositions for bonding magnets are shown in Table 9.

[0094]

[0095]

[0096]

[0097]

[0098] It was confirmed that, compared to the bonding magnet resin composition of Comparative Example 1 which did not contain a polyamide-based thermoplastic elastomer, the bonding magnet resin composition according to this embodiment yielded molded articles with excellent impact resistance and thermal shock resistance. In the molded articles of the bonding magnet resin composition of Example 7, which used a relatively large amount of polyamide-based thermoplastic elastomer, excellent impact resistance and thermal shock resistance were confirmed, but the strength retention rate after the heat aging test was lower. Furthermore, in the bonding magnet resin composition of Comparative Example 2, which contained a polyamide-based thermoplastic elastomer with a melting point of 172°C, a decrease in the yield rate during the thermal shock resistance test was observed.

[0099] Comparative Examples 3-7 used resin compositions for bonding magnets containing thermoplastic elastomers other than polyamide-based thermoplastic elastomers. The resin compositions for bonding magnets in Comparative Examples 3 and 4 had low flowability. Therefore, molded articles could not be obtained from these resin compositions for bonding magnets. In the resin compositions for bonding magnets in Comparative Examples 5-7 containing thermoplastic elastomers other than polyamide-based thermoplastic elastomers, a decrease in yield was observed in the thermal shock resistance test. Furthermore, the strength retention rate after the heat aging test was also low.

[0100] Industrial availability

[0101] Therefore, molded articles obtained using the resin composition for bonding magnets according to this embodiment exhibit high magnetic and physical properties. At the same time, these molded articles possess resistance to thermal shock, allowing them to be used even in harsh environments. Furthermore, these molded articles exhibit resistance to heat aging and maintain excellent physical properties even after exposure to thermal environments. Therefore, the resin composition for bonding magnets according to this embodiment is suitable as a material for bonding magnets.

Claims

1. A resin composition for bonding magnets, comprising at least magnetic powder, PPS resin, and a polyamide-based thermoplastic elastomer. The polyamide-based thermoplastic elastomer has a melting point of 130°C to 170°C.

2. The resin composition for bonding magnets according to claim 1, wherein, The polyamide-based thermoplastic elastomer has a Shore hardness D of 35 to 60.

3. The resin composition for bonding magnets according to claim 1 or 2, wherein, The polyamide-based thermoplastic elastomer has a tensile elongation of over 400%.

4. The resin composition for bonding magnets according to claim 1 or 2, wherein, The content of the polyamide thermoplastic elastomer relative to the PPS resin is 3.0 to 20.0 by weight.

5. The resin composition for bonding magnets according to claim 1 or 2, wherein, The content of the PPS resin is 5-30% by weight.

6. The resin composition for bonding magnets according to claim 1 or 2, wherein, The content of the polyamide-based thermoplastic elastomer is 0.4 to 2.6% by weight.

7. A bonded magnet, which is obtained by molding using the bonded magnet resin composition according to claim 1 or 2.

Citation Information

Patent Citations

  • Plastic magnetic composition

    JP1992044304A

  • Composite for plastic magnet

    JP1997219312A

  • Composition for bond magnet and bond magnet using the same

    JP2013253219A